Pengaruh Media Pembelajaran dan Pengalaman Mengajar Guru Terhadap Motivasi Belajar Siswa di Sekolah - Eddi Supriadi (Jurnal Pendidikan Educandum, 2025)
This research aims to analyze the influence of teaching media and teachers' teaching experience in order to enhance students' motivation to learn in schools. This study employs a quantitative method to investigate the extent of the impact that teaching media and teachers' teaching experience have on students' motivation. A sample of 69 teachers was used, and data were collected using questionnaires and analyzed through descriptive and inferential analysis. The study findings indicate that learning media have a positive and significant effect on increasing students' learning motivation, as do teachers' teaching experiences, which also have a positive and significant impact on students' learning motivation. Therefore, it can be stated that in the effort to enhance students' learning motivation in schools, the use of effective and efficient learning media, along with the presence of highly experienced teachers, can be instrumental.